Analisa Perbandingan Risk Dan Return Pada Investasi Saham Syariah Dan Konvensional (Studi pada Jakarta Islamic Index (JII) dan Indeks LQ45 Periode 2016-2019) - Lina Listyawati; Nurchayati Nurchayati (Serat Acitya, 2020)
This study aims to determine the average difference in Risk and Return of Islamic stocks in the Jakarta Islamic Index (JII) with conventional shares in the LQ45 Index in the period 2016 to 2019. This type of research is a descriptive study with a qualitative approach. This study uses the Probability Sampling method, while the sampling method used is saturated sampling. The research data was taken from the Indonesia Stock Exchange website www.idx.co.id and Yahoo Financial finance.yahoo.com as a provider of secondary data in the form of the names of issuers included in the JII and LQ45 Index as well as daily stock closing price data for the 2016-2019 period.Data analysis techniques used in this study are descriptive and inferential statistical analysis. This study shows that the average daily return of Islamic stocks is smaller than conventional shares, but the risk of Islamic stocks is greater than conventional shares in a period of 4 years. In statistical tests using the Independent Test T test with a significance level of 5%, the results show that there is no significant difference in risk and return between Islamic stocks and conventional shares in the sense that the risk and return between Islamic and conventional stocks are the same.